2009
DOI: 10.1080/09291010701794404
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and lifestyle habits in morning and evening types of human circadian rhythm

Abstract: Current lifestyles often involve activities during the day and at night, and disruption of habits and sleep-wake rhythms may result in circadian rhythm disorders. We assessed the sleep habits and lifestyle habits in 52 subjects using the Japanese-language version of Horne and Ostberg's Morningness-Eveningness Questionnaire and the Tokyo Neurosciences General Laboratory Formula Examination of Life Habits. Of the 52 subjects, 9.6% were morning-types, 71.2% were intermediate-types, and 19.2% were evening-types. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The administration in the hospital under study did not, however, arrange shifts according to chronotype. Evening type participants were shown to have more negative habits than morning types ( 14 ). Morning-types had early sleep schedules and circadian rhythms, and regular waking-, bed-, and sleep-time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The administration in the hospital under study did not, however, arrange shifts according to chronotype. Evening type participants were shown to have more negative habits than morning types ( 14 ). Morning-types had early sleep schedules and circadian rhythms, and regular waking-, bed-, and sleep-time.…”
Section: Discussionmentioning
confidence: 99%
“…Evening types, on the other hand, had late sleep schedules and circadian rhythms, and irregular waking-, bed- and sleep-time. Also, evening-types experienced more common irregular sleep and lifestyle habits, and dissatisfaction with the sleep ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep quality is also associated with chronotype: individual differences in time-of-day preference [37] , [38] . It has been found that evening-types (who prefer later bed and rising times), have less regular sleeping habits, less time in bed during the week, and more time in bed at weekends [39] , [40] . Poorer subjective sleep quality and more daytime sleepiness are also more frequent in evening-types [41] , [42] , [43] , who also consume more alcohol, caffeine, and tobacco [39] , [41] , [43] , [44] and report more emotional and psychological problems, such as anxiety and depression [38] , [42] .…”
Section: Introductionmentioning
confidence: 99%
“…Cortesi et al (2004) found that sleep/wake schedule irregularity increased with age and was associated with poor sleep, higher level of drowsiness, and tendencies to fall asleep during lessons and to report more accidents. ''Evening-types'', contrary to ''morning-types'', tend to have late sleep schedules, irregular waking time, bedtime, and sleep time, and are more often dissatisfied with their sleep (Wittmann et al 2006;Sukegawa et al 2009). Although sleep habits and circadian preference (i.e.…”
Section: Introductionmentioning
confidence: 99%